2008
DOI: 10.1186/1744-9081-4-15
|View full text |Cite
|
Sign up to set email alerts
|

Speech identification and cortical potentials in individuals with auditory neuropathy

Abstract: Background: Present study investigated the relationship between speech identification scores in quiet and parameters of cortical potentials (latency of P1, N1, and P2; and amplitude of N1/P2) in individuals with auditory neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 18 publications
6
35
1
2
Order By: Relevance
“…The findings of this study agree with those of Narne and Vanaja, 2008, in which they found that the amplitude of N1-P2 in auditory neuropathy was significantly smaller and that the latencies were significantly longer than those of normal adults. Their findings support the idea of abnormal cortical N1-P2 recordings in ANSD [13] .…”
Section: Pta (Db) Wds (%)supporting
confidence: 92%
See 2 more Smart Citations
“…The findings of this study agree with those of Narne and Vanaja, 2008, in which they found that the amplitude of N1-P2 in auditory neuropathy was significantly smaller and that the latencies were significantly longer than those of normal adults. Their findings support the idea of abnormal cortical N1-P2 recordings in ANSD [13] .…”
Section: Pta (Db) Wds (%)supporting
confidence: 92%
“…Their findings support the idea of abnormal cortical N1-P2 recordings in ANSD [13] . Rance suggests that the prolonged latencies could be due to dys-synchronous firing rate in those patients [17] .…”
Section: Pta (Db) Wds (%)supporting
confidence: 82%
See 1 more Smart Citation
“…Though individuals with auditory dys-synchrony have abnormal (or absent) ABRs, it is possible to elicit late latency responses (LLRs) from these individuals for a variety of stimuli [11][12][13] . Starr et al [3] were the first to relate LLRs and speech perception in individuals with auditory dys-synchrony.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Rance et al [10] were able to link observed improvements in aided speech identification to the presence of recordable cortical event-related potentials in their subjects. Narne and Vanaja [12] classified their subjects with auditory dys-synchrony into two groups, namely good and poor performers, based on their speech identification scores. They recorded click-evoked LLRs for their subjects and found that the N1-P2 amplitudes were significantly greater in good performers than in poor performers.…”
Section: Introductionmentioning
confidence: 99%